Establishing and validating the fluorescent amyloid ligand h-FTAA (heptamer formyl thiophene acetic acid) to identify transthyretin amyloid deposits in carpal tunnel syndrome. (3rd April 2017) - Hahn, Katharina; Nilsson, K. Peter R.; Hammarström, Per; Urban, Peter; Meliss, Rolf Rüdiger; Behrens, Hans-Michael; Krüger, Sandra; Röcken, Christoph
Abstract: Transthyretin-derived (ATTR) amyloidosis is a frequent finding in carpal tunnel syndrome. We tested the following hypotheses: the novel fluorescent amyloid ligand heptameric formic thiophene acetic acid (h-FTAA) has a superior sensitivity for the detection of amyloid compared with Congo red-staining; Amyloid load correlates with patient gender and/or patient age. We retrieved 208 resection specimens obtained from 184 patients with ATTR amyloid in the carpal tunnel. Serial sections were stained with Congo red, h-FTAA and an antibody directed against transthyretin (TTR). Stained sections were digitalized and forwarded to computational analyses. The amount of amyloid was correlated with patient demographics. Amyloid stained intensely with h-FTAA and an anti-TTR-antibody. Congo red-staining combined with fluorescence microscopy was significantly less sensitive than h-FTAA-fluorescence and TTR-immunostaining: the highest percentage area was found in TTR-immunostained sections, followed by h-FTAA and Congo red. The Pearson correlation coefficient was .8 (Congo red vs. h-FTAA) and .9 (TTR vs. h-FTAA). Amyloid load correlated with patient gender, anatomical site and patient age. h-FTAA is a highly sensitive method to detect even small amounts of ATTR amyloid in the carpal tunnel. The staining protocol is easy and h-FTAA may be a much more sensitive procedure to detect amyloid at an earlier stage.